Remittances, household development and poverty: A district-level analysis of Punjab, Pakistan / Kashif Imran - Kashif , Imran (2017)
Migrant remittances can play a critical role in the development (human development and poverty eradication) of households (HHs) in the country of origin. There is however still a lack of understanding on the developmental outcomes of remittance inflows given the limited number of micro-level analysis at the sub-national levels for migrant sending countries in South Asia. The Punjab province in Pakistan provides an excellent laboratory for a detailed case study on the sub-national developmental impacts of migrant remittances for the following reasons: First, it is the largest province of Pakistan, which houses 36 districts. Second, it is the largest recipient of remittance inflows to Pakistan, reflecting the nature of migrant-based HHs. The objectives of the study are threefold: First, to construct a new household-based human development index (HHDI), comprising sub-indices of education, health and housing. Second, to empirically examine the interactions between remittances and HHDI. Third, to empirically assess the impact of remittances on the incidence and severity of poverty. The remittance-HHDI and remittance-poverty nexuses are compared across districts, and at the intra-district urban-rural context. The study employs high quality household survey data based on the latest Multiple Indicators Cluster Survey (MICS, 2014-15) for Punjab. A sample of 36,400 HHs were chosen for the study. The key findings of the study are summarized herein. The HHDI reveals that not all districts in Punjab can be categorized as ‘low development’ as alluded to by the national human development index (HDI). Instead, medium levels of human development are noted for districts with high and low remittance inflows. The results also support the importance of decomposing the HHDI into its sub-indices. In examining differences in human development between migrant HHs and non-migrant HHs, the results indicate that the core sub-index that should not go unnoticed is the housing environment (considered as material wealth or assets and standard of living). Non-migrant HHs seem to be worse off or deprived in terms of their housing environment (facilities and conditions) relative to remittance receiving HHs. Further, the empirical results on the remittance-HHDI nexus suggest that migrant HHs are relatively better-off than non-migrant HHs across most of the districts in Punjab, after controlling for HH characteristics and features specific to the HH head. Disaggregated estimations of HH development again indicate that remittances matter for development in terms of housing for most of the districts in Pakistan. Additionally, the remittance-poverty analysis implies that the probability of being poor among migrant HHs is significantly lower than the non-migrant HHs in all districts of Punjab. The implications that follow from the findings are: First, the study supports the feasibility of quantifying human development at the sub-national HH-level, as the newly constructed HHDI confirms the varying levels of human development across the districts of Punjab. Second, the study suggests that migrant remittances are most likely to increase inequalities in the development of housing and poverty disparities between migrant- and non-migrant HHs in all districts of Punjab. The government therefore needs to balance its focus on education and health with housing, when providing developmental assistance to the HHs in Punjab. The target group of HHs to be given priority should be those located in districts with the highest incidence of poverty and lowest HHDI, namely HHs in South Punjab.